The role of mothers and fathers in the sexuality education of their children: a cross sectional study. - Downie, Jill (Curtin University, 1998)
This study examined the roles of mothers and fathers in the sexuality education of their sons and daughters. Specifically, the research investigated the sexuality knowledge, attitudes and skills of parents to provide education to their pre-school (5 years of age) or year seven (12 years of age) children. Investigation of parents' active participation in the sexuality education of their children and analysis of the factors which determined their involvement was the main objective of the study. The comfort level of parents in their communication with their children and plans for further sexuality education were also considered. Predictive models of sexuality communication were empirically tested and from this a conceptual model was derived which explicates sexuality education in the home.The research involved both a qualitative and quantitative approach to the investigation of parents' contribution to the future sexual health of their children. The first phase of the study involved focus group interviews with 11 parents to discuss their issues and concerns in providing sexuality education. Thematic analysis of the focus groups and review of the literature informed development of the instrument used in the second phase of the study.Face validity of the instrument was established and 371 parents participated in phase two of the study. One hundred and ninety five (195) mothers and 176 fathers responded voluntarily to an anonymous, self-administered questionnaire on their involvement in their child's sexuality education.In the second phase of the study the instrument used included demographic data and general questions regarding sexuality education. A sexuality knowledge and attitude scale was included as well as qualitative questions concerning parents' skills in sexuality education pertaining to three relevant scenarios. Parents' teaching practices, plans for future sexuality education and a Likert scale of comfort levels was also part of the instrument.Demographic data was consistent with the general population except with respect to income and education which were both higher than expected. Most parents (95%) stated that the home should be the primary place for sexuality education. However, less than half (36%) initiated frequent discussion with their child.Results showed that generally parents had a satisfactory knowledge of sexuality (M= 2 1) but that mothers had more knowledge of sexuality than fathers. Parents' sexuality attitudes tended toward the conservative end of the continuum with fathers more liberal in their attitudes than mothers. The study revealed a small positive correlation between knowledge and attitudes which showed that parents with more knowledge had more liberal attitudes.Mothers' and fathers' skills in sexuality education varied, demonstrating some uncertainty in this aspect of parenting. Most parents (63%) were not appropriate in their response to their child's questions about 'how babies are made', and provided their child with no factual information. Although most parents (76%) had observed their child's 'genital play' the majority (75%) were unaware of their child's 'sex play' behaviours. Parents' skills in responding to their child's genital play and sex play revealed that few (less than 16%) demonstrated complete acceptance of their child's sexual behaviour. Curiously, parents stated that they were generally comfortable when presented with all situations. The findings indicate a need for community based parent education which focuses on enhancing parents' sexuality knowledge, attitudes and skills.Generally small percentages of parents talked to their children about various sexuality topics with the factual topics such as body differences, birth, reproduction and obscene words the most frequently discussed. Other topics, of a more sensitive or intimate nature, such as contraception, sexually transmissible diseases, abortion, dating, intimate relationships, masturbation, petting and wet dreams were discussed by fewer parents. Not unexpectedly, parents communicated more with their year seven child than their pre-schooler, but the ages at which topics were introduced varied widely. This suggests parents require guidelines for their role which promote early, open and unreserved communication. The timing of sexuality education is also crucial to ensure that sexuality is as integral to the individual as numeracy and literacy and is approached in the same manner.For almost all topics mothers communicated more than fathers for both the pre-school and year seven groups. In contrast to the literature, pre-school mothers communicated equally with both genders and fathers communicated more with their sons, while by year seven, both mothers and fathers communicated more with their sons than their daughters. The topics discussed with sons and daughters appeared to differ with both mothers and fathers discussing physiological and protective issues with daughters and conversing about sexual behaviours with sons. Gender was a significant factor in sexuality education and strategies to promote equality relating to both parents and children are required.Many parents severely overestimated their plans for communicating with their children about sexuality. Most parents of pre-school children planned to discuss all sexuality topics by the time their children were 12 years old, but in reality this was not evident when compared with the year seven group. Few children initiated frequent communication (37%) with their parents but when they did it was usually with their mother.For the overall sample, the communication of sexuality was predicted by parents' attitudes to teaching sexuality, their perceived preparation, the church as a source of sexual learning and their teaching skills. The predictors however, varied depending on the gender of the parent and the age group being considered and different models explained between 14% and 46% of the variance of communication.No previously published research in Australia has investigated the role of mothers and fathers as sexuality educators. This study has contributed to the increasing body of knowledge in sexuality which aims to educate children more comprehensively for sexual health in adulthood. The conceptual framework derived from the literature and the findings of the study is anticipated to be of benefit to health professionals, school teachers and sexuality educators as they work with parents to promote sexual health.